A comprehensive study on development of a small-sized self-propelled robot for bridge inspection. Issue 8 (3rd August 2017) - Akutsu, Ayako; Sasaki, Eiichi; Takeya, Koichi; Kobayashi, Yusuke; Suzuki, Keigo; Tamura, Hiroshi
Abstract: Application of maintenance to ensure the safety, extend the service life and reduce the life-cycle cost of civil structures is important. In this paper, a new inspection method is proposed using a robot which can effectively approach target sections of structures, such as areas that are either too narrow or too dangerous to approach and perform both visual and detailed inspection with various devices. The small-sized self-propelled robot was initially developed. The test model can freely move on the surfaces of various types of structures. Next, the function to detect the deterioration of concrete or steel surfaces by attached cameras to the robot was examined. Moreover, a function was installed to identify the location of the robot automatically using a phase-only correlation method and to determine structural behaviours using an accelerometer. Finally, the applicability of robotic movement and all installed functions was tested on an existing bridge.